(untitled) (Global Journal of Medical Research, 2013)
Prenatal care is universally considered important for women and children. This study aims to assess the knowledge of women beneficiaries of ICDS centres related to prenatal care belonging to district Budgam of Kashmir region. Nursing mothers (NM), Pregnant women (PW) and Mother of children beneficiaries (MCB age 6 months-3years) were included to assess and compare the their awareness levels. A total of 600 women beneficiaries were randomly selected from four blocks of district Budgam (150 from each block). The results of the study revealed that majority (79.1%) of the respondents were aware of the importance of medical consultation during pregnancy and about 48.6% were fully aware with appropriate time of consultation. Almost all respondents were aware of weight monitoring during pregnancy but not about its significance. Respondents were also aware about the doses and time schedule of TT vaccination during pregnancy. Basic pre-natal care components are effective means to prevent range of pregnancy complication and reduce maternal mortality. The findings indicate that there is need for enhancement of intervention educational programme in ICDS regarding importance of prenatal care and service for the healthy birth outcome and mothers’ well being.